Studies on Calcium Ion Selectivity of ZnO Nanowire Sensors Using Ionophore Membrane Coatings. (8th January 2009) - Asif, M. H.; Nur, O.; Willander, M.; Yakovleva, M.; Danielsson, B.
Abstract : Zinc oxide nanorods with 100 nm diameter and 900 nm length were grown on the surface of a silver wire (0.25 mm in diameter) with the aim to produce electrochemical nanosensors. It is shown that the ZnO nanorods exhibit a Ca 2 + -dependent electrochemical potentiometric behavior in an aqueous solution. The potential difference was found to be linear over a large logarithmic concentration range (1 μ M to 0.1 M) using Ag/AgCl as a reference electrode and the response time was less than one minute. In order to adapt the sensors for calcium ion measurements in biological fluids with sufficient selectivity and stability, plastic membrane coatings containing ionophores were applied. These functionalized ZnO nanorods sensors showed a high sensitivity (26.55 mV/decade) and good stability.